Effect of thermal radiation on mixed convection of a nanofluid from an inclined wavy surface embedded in a non-Darcy porous medium with wall heat flux - D. Srinivasacharya; P.Vijay Kumar (Propulsion and Power Research, 2018)
This article focuses on the effect of radiation on mixed convection in a nanofluid along an inclined wavy surface embedded in a non-Darcy porous medium. A coordinate transformation is employed to transform the complex wavy surface to a smooth surface. The governing equations are transformed into a set of partial differential equations using the non-similarity transformation and then a local similarity and non-similarity method is applied to obtain coupled ordinary differential equations. These resulting equations are linearized using the successive linearization method and then solved by the Chebyshev spectral method. The effects of radiation, non-Darcy parameter, Brownian motion parameter, thermophoresis parameter, the amplitude of the wavy surface, angle of inclination of the wavy surface on the non-dimensional heat and nanoparticle mass transfer rates are studied and presented graphically. Keywords: Mixed convection, Nanofluid, Inclined wavy surface, Non-Darcy porous medium, Radiation, Heat flux